Session mobility in multimedia services enabled by the cloud and peer-to-peer paradigms - Johansson, Dan (2011 IEEE 36th Conference on Local Computer Networks, 2011)
Services based on new information technology offering audio and video modality are viewed among the most important today. When users change location or device there is a need to keep these media sessions active. The main purpose of this article is to present a lightweight framework that allows session mobility through making profit of the cloud and peer-to-peer paradigms, while at the same time fulfilling the prevailing requirements for new session mobility multimedia services. We demonstrate the principles of the framework by creating a real prototype, allowing combined video and audio sessions to be migrated between devices, thus showing successful implementation of session mobility meeting requirements such as low degree of service provider dependency, no changes to current common network infrastructure, dealing with privacy issues, providing flexibility and low cost, and letting the user control when and where to migrate the sessions. It is our belief that relatively new paradigms such as peer-to peer computing and cloud services could enhance and support flexible session mobility in a mobile use context.